Pengaruh Daya Tarik Perusahaan, Reputasi Perusahaan, dan Rekrutmen Online Terhadap Minat Melamar Kerja Generasi Y dan Z Muslim Pengguna Platform Tik-Tok Pada PT Kelas Digital - Junaedi, Muhammad Ali Ridwan; Dewianawati, Dwi; Agustina, Ratna (ITB AAS INDONESIA Surakarta, 2024)
This research aims to determine the influence of company attractiveness, reputation and online recruitment on interest in applying for work using the Tik-Tok application. The population used is GENERATION Y AND Z Muslims aged between 15 and 41 years who use the Tik-Tok application. From the results of these calculations, a sample of 96 people were obtained as respondents. The research was carried out using multiple linear regression analysis tests. Based on the test results, it can be concluded: Company attractiveness has a positive influence on interest in applying for work, company reputation has a positive influence on interest in applying for work, online recruitment has a positive influence on interest in applying for work.